Effect of pvp addition in the preparation of polyethersulfone (PES)–AgNO3 antibacterial membrane - Basri, H.; Ismail, A. F.; Aziz, M. (2009)
Association of antibacterial agent into polymer–based material is an interesting, recent extension in membrane technologies research area. Asymmetric polyethersulfone–silver nitrate (PES–AgNO3) nanocomposite membranes were synthesized by wet phase inversion with polyvinylpyrrolidone (PVP) as additive. Three different molecular weights (MW) of PVP in the range of 10 K to 360 K were tested for their ability to stabilize and disperse silver in the polymer solution. Results showed that PVP 360 K plays a significant role in altering silver particle size with better dispersion compared to the membranes prepared without addition of PVP and with the addition of lower MW of PVP. Results agreed with the leaching detected by ICP–MS where silver loss during membrane fabrication for PES–Ag–P360 is only 0.4636 ppm (0.0093%). The antibacterial activity for the resultant membranes was tested using inhibition zone method. Results indicated that PES–AgNO3 and PES–AgNO3–PVP (loaded with only 0.5 wt% silver) were antibacterial to Escherichia coli and Staphylococcus aureus. The improvement of antibacterial properties of the prepared membranes could be primarily attributed to the PVP addition as well as the surface morphology and permeation properties